INFECTIVITY OF BLOOD FROM A LOW-LEVEL HBV CARRIER - Chiyoda, Shin; Inoue, Junko; Aguin, Tamaka; Mitutomi, Yosirou; Oda, Hidetaka; Ezaki, Tosinobu (Journal of the Japan Society of Blood Transfusion, 2002)
Blood safety as regards transfusion-transmitted viral infection is of great concern. Recently, the incidence of post transfusion hepatitis B virus (HBV) infection has decreased through the introduction of more sensitive screening, such as hepatitis B surface antigen (HBsAg), anti-HBV core antibody (anti-HBc) and nucleic acid amplification test (NAT), as well as the registration of screened donors. However, the risk of HBV infection due to blood transfusion still persists. We experienced a case of HBV infection by blood transfusion in a 75-year-old man suffering from chronic pancreatitis and pyloric stenosis. He received blood units from eight donors for gastrectomy on Nov. 22, 2000. Although hepatitis was not suspected, laboratory studies for liver function were carried out. Twelve weeks after transfusion, HBsAg was found in his serum on Feb. 13, 2001. The 8 donors' retained blood was tested by the individual nested PCR method, and one was found to be positive. To investigate a causal relationship, HBV DNA nucleotide sequences of the patient and donor were analyzed. Sequences concurred in both and belonged to genotype C with mutation of core promoter. These findings revealed that post-transfusion hepatitis cannot be completely prevented in spite of the introduction of sensitive screening containing NAT. Patients who receive transfused blood units should undergo follow-up testing for hepatitis virus.